2012
DOI: 10.1007/s10800-012-0396-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of anode and cathode flow field depths on the performance of liquid feed direct methanol fuel cells (DMFCs)

Abstract: The effect of the anode and cathode flow field depths on the performance of a single cell Direct methanol fuel cell (DMFC) of 45 cm 2 active area were experimentally investigated. Double serpentine flow fields (DSFFs) with varying channel depth namely, 0.2, 0.4, 0.6, 0.8, and 1 mm but with fixed channel and rib width each of 1 mm on both anode and cathode were designed, fabricated, and tested. The experimental study involved measurement of pressure drops across anode and cathode flow field plates, polarization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…First, a comparison between the obtained results of the polarization curve and the measurements by Vijayakumar et al 40 was conducted, as shown in Figure 4a. First, a comparison between the obtained results of the polarization curve and the measurements by Vijayakumar et al 40 was conducted, as shown in Figure 4a.…”
Section: Model Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…First, a comparison between the obtained results of the polarization curve and the measurements by Vijayakumar et al 40 was conducted, as shown in Figure 4a. First, a comparison between the obtained results of the polarization curve and the measurements by Vijayakumar et al 40 was conducted, as shown in Figure 4a.…”
Section: Model Validationmentioning
confidence: 99%
“…As indicated in the figures, the net power is calculated based on deducting the pumping power from the produced power by multiplying the current and voltage. 40 Comparisons of the maximum output power and pumping power losses for all investigated designs for serpentine and spiral flow fields are shown in i and ii of Figure 12c, respectively. It is clear that decreasing the channel height from 0.8 to 0.2 mm significantly increases the electric power output for all configurations.…”
Section: Overall Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Also, there was more uniform fuel distribution due to higher pressure drop between inlet and outlet. Vijayakumar et al [24] studied the effect of channel depth on cell performance. They reported that a 0.4 mm depth on both anode and cathode exhibits the best cell performance due to low channel volume.…”
Section: Original Research Papermentioning
confidence: 99%
“…Current collector plates in large DMFC stacks are commonly designed and fabricated following the same strategies as for hydrogen fed PEM fuel cells, using graphite as substrate [51,52], although stainless steel anode and cathode current collectors are used in passive stacks [53][54][55]. However, the main interest in the current collector materials and flow fields design is triggered during the last decade due to the increasing interest for the development of micro direct alcohol fuel cells (μDAFC), after Kelley et al fabricated a miniature DMFC [56].…”
Section: Current Collectors and Flow Fieldsmentioning
confidence: 99%